Comparison of serum iron, hemoglobin, ferritin and CRP levels in prostate cancer patients with a control group (Annals of Medical Research, 2023)
Aim: The aim of the study was to investigate the differences between serum iron, ferritin, hemoglobin, and CRP levels between patients with new prostate cancer diagnosis and a control group.Materials and Methods: This study was cross-sectional and prospectively recorded data from 323 patients with new prostate cancer (PCa) diagnosis and 346 healthy controls between April 2015 and June 2022. Parameters like age, PSA value, serum iron, ferritin and hemoglobin were compared between groups.Results: The age distribution in groups was identified as 67.19±8.33 years in the PCa group and 62.11±8.16 years in the control group (p